Karakteristik Hasil CT-Scan Kepala pada Penderita Cedera Kepala di Rumah Sakit Dr.H.Abdul Moeloek periode Januari – Desember Tahun 2018 - Muhamad Yunus; Alfi Wahyudi; Arti Febriyani H; Rona Asla Romiza (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Computerized Tomography (CT) -Scans examination are the main choice modalities in patients with acute head injuries because they are able to view the entire brain tissues and accurately distinguish the nature and presence of intracranial lesions and Extracranial. This study aim to determine the characteristics of results CT-Scan head on the patient's head injury at Dr.H.Abdul Moeloek Hospital January to December Period 2018. The research is a descriptive study with a crosssectional approach. The samples in this study were all records of medical head injury patients at Dr.H.Abdul Moeloek Hospital in January – December 2018 based on the formula Slovin as many as 182 respondents. The sampling techniques in the study used purposive sampling techniques. Data analysis using univariate analysis. From 182 respondents known prevalence of the age of the patient's head injury is 16-25 years as many as 82 respondents (45.1%), male gender 119 respondents (65.4%), a mild head injury of 105 respondents (57.7%). A normal CT-Scan overview of 99 respondents (54.4%) With a valid description (subarachnoid hemorrhage) as much as 25 respondents (13.7%). Characteristics of results CT-Scan head at the head injury sufferer of most ages 16-25 years, most male gender, most dominant mild head injuries and CT-Scan results most commonly present normal results with description SAH (subarachnoid hemorrhage).